Geology of the Roman Catholic Basilica of St. John the Baptist, St. John's, Newfoundland - Pollock, Jeff (Geoscience Canada, 2004)
SUMMARY The Basilica of St. John the Baptist was constructed in the form of a Latin cross and in the Lombard Romanesque style of a Roman Basilica. The cornerstone was laid in 1841 and construction continued for the next 14 years until the church was consecrated in 1855. The foundations were built using local sandstone from Signal Hill; Galway limestone and Leinster granite from Ireland were used for the exterior walls and towers. Small amounts of sandstone from the Kellys Island and Mistaken Point formations were quarried and used in the ambulatory walls. Signal Hill Group sandstone was used in the restoration of the exterior walls. The impressive statuary throughout the Basilica were carved in Carrara Marble, quarried in Italy. Verona limestone, also from Italy, was used to construct parts of the high altar, while the side altars were adorned with Egyptian travertine.